Islam in Malabar (1460-1600) : a socio-cultural study - Panakkal, Abbas (Kulliyyah Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research is a study on 16th century Malabar Muslims and their approaches to religion and culture in a multi-faceted society. Malabar, situated in the most southern state of India called Kerala, is a unique coastal region, which was reached by Islam at the time of the Prophet (Peace Be Upon Him). This study explores how Malabar Muslims maintained a moderate methodology to continue peaceful coexistence in the region. The 16th century was an era of reformation in Malabar with a number of specialties like the establishment of its first graduate school in Ponnani by Zainuddin Makhdum I, the composition of the first history book by a Malabari scholar, Sheik Zainuddin Makhdu II, and the earliest poems in the Malayalam language (the mother tongue of the region) by the Muslim judge and sage Qazi Muhammed. The century also witnessed a remarkable inception of naval activities in India pioneered by Malabar Muslims. Moderation, a reflecting terminology used several times in the Holy Qur'an, was a prime agenda of Malabar Muslims in the 16th century, executed by prominent religious leaders who led a dazzling moral life, which became a model for generations. This study probes the realities of Malabar Muslims, who profusely used traditional lifestyles, food habits, songs and architecture to incorporate the general public to their realm of belief. The moderate approach of the Malabar society created a unique Muslim folk culture, representing a great attempt to Islamize the traditional culture of Malabar. In this context it is very important to bring out a study on the time-tested moderate approaches of Islam, which paved the way for the wide acceptance of Islam in Malabar.